Antihypertension Medication Usage Pattern and Predictors of Evidence-based Medication among Hypertension patients - Iqbal, Muhammad Shahid (Asian Journal of Pharmaceutics (AJP), 2020)
Background: Despite substantial guidelines on the effective management of hypertension, many studies demonstrated an underutilization of evidence-based medicine (EBM) for the treatment of hypertension patients. This study aimed to evaluate the antihypertension therapy and the impact of patients’ specific predictors on the utilization of EBM among hypertension patients. Materials and Methods: A retrospective observational study designed to investigate the prescribing trends and patient’s factors (predictors) affecting the utilization of antihypertensive medications. Patients’ factors included age, gender, ethnicity, smoking status, and concurrent medical conditions. The study was conducted using a purpose-developed data collection form to assemble the patient’s information. Results: A total of 170 hypertensive patients, comprising 83 males (48.82%) and 87 females (51.18%) were selected as subjects for this study. The findings suggested that the mean age of our study population was 59.32 years and 70% of them had two to three comorbidities. It was established that 98.8% of the patients had chronic kidney disease and 35.3% of them were in Stage V. Diuretics were the most commonly prescribed antihypertensive class under monotherapy. Conclusion: This study evaluated antihypertension medications usage pattern and patients’ predictors affecting utilization of antihypertension medications among hypertension patients.